Assessing the MaDiH CKAN catalogue as an engagement tool for the Jordanian cultural heritage community. (4th May 2022) - Mubaideen, Shatha; Flohr, Pascal; Smithies, James; Bala'awi, Fadi; Palmer, Carol; Idwan, Sahar; Esposito, Alessandra
Abstract : MaDiH (Mapping Digital Cultural Heritage in Jordan) was a two-year UK-Jordanian project that aimed to identify essential systems, datasets and standards to contribute to the long-term sustainable development of Jordan's digital cultural heritage. The project launched an online catalogue and prototype repository using the Comprehensive Knowledge Archive Network (CKAN) platform to present the collected data that was produced by the local and international research community on Jordan's cultural heritage. This paper assesses the usability of the MaDiH CKAN catalogue using qualitative and quantitative methods. A thorough analysis of the project's user engagement activities and online presence was undertaken to identify current and potential future uses of the CKAN catalogue by its research community. The preliminary analysis indicated that the largest user group were mid-senior to senior academics/professionals from the cultural heritage sector. Therefore, representatives of this group were selected for further usability analysis through semi-structured online interviews, in order to validate the research outcomes and get deeper insights into the research domain. The findings offer significant insights for similar digital cultural heritage initiatives in Jordan, as well as recommendations for the future development of the MaDiH CKAN catalogue as a National Heritage Portal repository.